Morcellation of the Uterus: Is There Any Place? - Halaska, Michael J; Gracia, Myriam; Laky, Rene; Zapardiel, Ignacio (Current oncology reports, 2020)
PURPOSE OF REVIEW: This paper aims to review recent findings related to uterine morcellation. RECENT FINDINGS: In 2014, the US Food and Drug Administration (FDA) issued a safety communication warning against the use of laparoscopic power morcellators. A risk of occult uterine sarcoma in women is 1/770 to 1/10,000. Our goal is to minimize the risk of spillage due to morcellation and balance it with other risks due to different surgical approaches. In case of a presence of sarcoma risk factors, any form of morcellation should be contraindicated. Power morcellation should be limited to myomectomies. In peri- and postmenopausal age, an endometrial biopsy is highly recommended before surgery with expected morcellation. It is important to explain to the patient the risks of morcellation and the risks and benefits of different surgical approaches. Finally, women should be informed that the prognosis of leiomyosarcoma is poor regardless of the method of removal.
Keywords: Laparoscopic hysterectomy; Oncological risk; Uterine sarcoma; Uterine Myomectomy; Sarcoma; Uterine Neoplasms; Uterus; uterus; Laparoscopy; morcelace; Myomectomy; ženské pohlaví; nádory dělohy; Humans; myomektomie; sarkom; Female; laparoskopie; Morcellation; lidé; Containment bags